2009
DOI: 10.1021/jp903982w
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Study of Electronic, Absorption, and Thermodynamic Properties of Crystalline Styphnic Acid and Its Metal Salts

Abstract: The electronic structure, absorption spectra, and thermodynamic properties of crystalline styphnic acid and its metal salts (potassium, barium, and lead styphnates) have been studied using density functional theory within the local density approximation. The results show that the metal states affect the electronic structure of styphnic acid by modifying the density of states of the O atoms of hydroxyls. The C-O bond fission may be favorable in the decomposition of styphnic acid and its metal salts. The absorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 41 publications
3
29
0
Order By: Relevance
“…Table 6 lists the band gaps of styphnic acid and its metal salts [33]. It is found that the band gap increases in the sequence of lead styphnate, potassium styphnate, barium styphnate, and styphnic acid.…”
Section: Styphnic Acid and Its Metal Salt Seriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 6 lists the band gaps of styphnic acid and its metal salts [33]. It is found that the band gap increases in the sequence of lead styphnate, potassium styphnate, barium styphnate, and styphnic acid.…”
Section: Styphnic Acid and Its Metal Salt Seriesmentioning
confidence: 99%
“…Their results show that energy transfer rates have a good correlation with the impact sensitivity of explosives. Our recent first-principles studies on energetic inorganic and organic crystals [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] indicate that there is the relationship between the band gap and impact sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction mechanism for the complexes can be studied in terms of the interaction between HOMO and LUMO orbitals of the structure. Many studies have proved that the HOMO-LUMO energy gap is an important parameter characterizing the activity of energetic materials [25][26][27][28][29][30]. HOMO and LUMO 3D plots are shown in Fig.…”
Section: Homo and Lumo Analysesmentioning
confidence: 99%
“…Lead styphnate (1), lead azide (3), (5-cyanotetrazolato-N 2 ) pentaammine cobalt perchlorate (4), and tris(carbohydrazide) zinc perchlorate (5) are widely used primary explosives and hexa(1,5-diaminotetrazole) cobalt perchlorate (2) is a very promising initiator composition, so the structures and properties of these compounds have been studied in detail [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]; their chemical structures are shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%